PENGUATAN LITERASI DIGITAL GEN Z DALAM PEMASARAN BISNIS DIGITAL DI SMK DARUL ULUM RANGKASBITUNG - BANTEN - Fitrianti, Rizqi; Endayani, Endayani; Susilawati, Eka; Adi Nugroho, Muhammad Ichsan (Gapenas Publisher, 2025)
Advances in digital technology in global competition are encouraging Generation Z to develop competencies in digital marketing. Therefore, through the ‘Gen Z Melek Digital’ training at SMK Darul Ulum – Rangkasbitung, Banten, digital literacy among students can be strengthened. The objective of this study is to encourage the formation of a mindset about digital entrepreneurship, particularly in vocational schools, by increasing interest in digital business through online platforms. This study employs a qualitative descriptive approach using data collection techniques such as observation, interviews, and documentation during the training. The research subjects are 12th grade students at SMK Darul Ulum – Rangkasbitung, Banten. The findings indicate that this enhancement plays a crucial role in preparing Generation Z to adapt to technological advancements aligned with industry needs. This training program is effective in improving students’ understanding of digital marketing, social media optimization strategies, and practical content creation skills. Based on these findings, digital literacy enhancement for Gen Z can be conducted continuously by collaborating with industry as a support for practical learning.